The Structure and Function of Ionotropic Receptors in Drosophila - Ni, Lina (Frontiers in Molecular Neuroscience, 2021)
Ionotropic receptors (IRs) are a highly divergent subfamily of ionotropic glutamate receptors (iGluR) and are conserved across Protostomia, a major branch of the animal kingdom that encompasses both Ecdysozoa and Lophothrochozoa. They are broadly expressed in peripheral sensory systems, concentrated in sensory dendrites, and function in chemosensation, thermosensation, and hygrosensation. As iGluRs, four IR subunits form a functional ion channel to detect environmental stimuli. Most IR receptors comprise individual stimulus-specific tuning receptors and one or two broadly expressed coreceptors. This review summarizes the discoveries of the structure of IR complexes and the expression and function of each IR, as well as discusses the future direction for IR studies.